175 Aortopathy-causing mutations increase aortic stiffness in healthy individuals. (6th June 2015) - Francis, Catherine; Marvao, Antonio de; O'Regan, Declan P; Dawes, Timothy JW; Alenaini, Wareed; Gandhi, Ajay; Quinlan, Marina; Buchan, Rachel; Barton, Paul J; Walsh, Roddy; John, Shibu; Cook, Stuart A
Abstract : Introduction: As gene sequencing becomes more widespread, the clinical implications of incidental findings in patients' genomes are becoming more complex. We identified healthy volunteers with mutations known to cause penetrant, Mendelian aortic disease, and examined the association of these mutations with aortic pulse wave velocity (PWV); a key marker of cardiovascular risk and aortic elastic function. Methods: We recruited 476 healthy volunteers with no known history of cardiovascular risk factors or disease for aortic phenotyping and gene sequencing. We measured aortic arch pulse wave velocity derived from Cardiovascular MRI (CMR) using ArtFun software and performed whole exome sequencing (Illumina HiSeq 2000). Sequence was alignedto hg19 reference using BWA v0.7.10 and variants were called using GATK and validated using IGV. Variants that are presumed causative for aortic disease were prioritised using HGMD and were further annotated by literature review. A binary variable, "AOV status" reflected the presence or absence of a variant linked with aortopathy by this approach. Statistical analysis was performed using linear regression modelling, Mann-Whitney U tests and bootstrapping in R. For Mann-Whitney U tests, we used age-corrected PWV [=PWV/log (Age)]. Results: 17 of our healthy volunteers (3%) had previously reported pathogenic mutations in seven aortopathy genes ( COL1A2, COL3A1, FBN1, MYH11, MYLK, TGFBR1 and TGFBR2 ; see Table 1). Three mutations (in 4 individuals; 0.8% of our cohort) had evidence for pathogenicity (eg family linkage analysis) beyond just a single case report; two in TGFBR2 (3 individuals) and one in COL1A2 . These four subjects had significantly higher aPWVs than control cases (Mann-Whitney U test; U=235, p = 0.01; see Figure 1 ), and than those cases where the evidence for variant pathogenicity was limited (p = 0.02). Linear regression modelling of PWV was significantly improved by the addition of AOV status (ANOVA of nested linear models; p = 0.03; F=5.56(1), R 2 =0.07; multiple R 2 =0.57; p < 0.001), and this improvement was more evident with bootstrapped linear regression (p < 0.01). Stepwise model selection by AIC prioritised AOV status in the final linear model, which included log (age), gender, MAP, pulse rate, body surface area and fat mass. Discussion: It is not unusual to find "disease-causing" variants in an apparently healthy population. Sometimes this is used to argue against the pathogenicity of a particular variant. However, our results imply that some of these "healthy" individuals may have penetrant aortic disease but of limited expressivity. These individuals may have increased risk of cardiovascular events, and so-called "spontaneous" aortic aneurysm and dissection. This finding therefore has implications for genetic counselling, as well as for the conduct of gene sequencing studies.